Inclusive Education: A Data Triangulation Study - Silva, Eliza França e; dos Santos Elias, Luciana Carla; Grande, Maria Catarina Leite Rodrigues; Abrahão, Anaísa Leal Barbosa [UNESP] (My University, 2024)
The inclusion of students with disabilities faces challenges in Brazil, despite legislative efforts. The literature documents the importance of social skills in this process. The present study aimed to verify and understand relationships between resources and difficulties in the inclusion process with the social skills and behavioral problems of students, the educational social skills of parents and teachers, and sociodemographic variables. This is a mixed study, with data triangulation. A total of 42 guardians and 34 teachers of 44 students with intellectual disabilities enrolled in public schools in Minas Gerais (Brazil) participated. The instruments used were a semi-structured interview, a questionnaire to characterize sociodemographic variables, the Social Skills Rating System (SSRS), the Parenting Educational Social Skills Interview Guide (Roteiro de Entrevista de Habilidades Sociais Educativas Parentais—RE-HSE-P), and the Teacher Educational Social Skills Inventory (Inventário de Habilidades Sociais Educativas de Professores—IHSE-Prof). The Iramuteq software program was used for triangulation. The first triangulation comprised qualitative data from interviews with guardians, quantitative data from the RE-HSE-P and SSRS instruments, and sociodemographic data referring to guardians and children. The second triangulation involved qualitative data from interviews with teachers, quantitative data from the IHSE-Prof and SSRS, in addition to sociodemographic data from teachers and students. Classes of resources and difficulties were identified. The triangulation regarding the guardians showed that variables relating to a positive repertoire of students’ social skills, absence of behavioral problems, and negative educational practices were associated in classes that involved resources. The triangulation for teachers signaled links between classes of resources and educational social skills above or on average; and in the difficulty classes, educational social skills were below average. It is concluded that programs to promote childhood social skills and educational social skills are relevant to this population.
Keywords: Behavior problems; Educational inclusion; Educational practices; Intellectual disability; Parents; Social skills; Teachers